Cubism and modernism (Modern art and modernism : Manet to Pollock, 1993)
Tackles a wide range of issues in modern art, including discussion of some theories on modernism by noted critic Theodore Greenberg. Discusses both the early and later phase of cubism, centered to the development of modern art, its relationship with the other movements such as post-impressionism, dadaism, surrealism, constructivism and others.